The Effect of Electricity Distribution Loos, Electricity Power Consumption, Electricity Intensity on Energy Consumption in West Africa - Atiku, Abubakar Mohammed; Ismail, Suraya; Roslan, Farah; Ahmad, Ali Umar (International Journal of Energy Economics and Policy, 2022)
This paper analyses the effect of electricity distribution loos, carbon emissions, growth, and energy consumption nexus in West Africa utilising pooled series data that spans the decades of 1970 to 2019. The paper employs cross sectional auto regressive distributive lag model (CS-ARDL), and Dumitrescu Hurlin Causality Test. The result of unit root test reveals that the variables have mixed stationary. In addition, the empirical analysis revealed a statistically significant negative relationship between electricity distribution losses on energy consumption while electricity intensity level, electricity power consumption and economic growth prevails positive on energy consumption in the log-run. The result established a unidirectional causal relationship running from energy consumption LEC to electricity distribution losses LEDL while a bidirectional relationship was found between electricity intensity level LEIL causing LEPC electric power consumption and carbon emission LCO2.